Biopolymer nanocomposites: their mechanical, thermal, and gas barrier properties for food packaging. Issue 1 (February 2021) - Andini, R; Sulaiman, M I; Martunis,; Umam, A H; Olivia, M; Endres, H J
Abstract: The food packaging industry is the largest sector of the plastic industry, accounting for 40% of the total (conventional) plastic demand. Conventional plastic packaging has significant practical advantages, in protecting packaged foods from contamination and the loss of food quality. Plastics are made up of repeating small units called ' monomers ' that bind together to form the long chains called ' polymers ' However, conventional plastics have detrimental effects human health, wildlife, and the environment. Many developing countries are overwhelmed with the plastic waste emitted to the oceans. Indonesia is the second biggest emitter of plastic waste, after China. Biodegradable plastics ( bioplastics, green plastics) are an alternative for saving our environment. Bioplastics or biopolymers, are made from at least 60% natural materials, mostly of plant based origin, but they have several drawbacks: (i) lower mechanical properties; (ii) bad thermal stability; (iii) relatively low gas barrier properties. This lab-based study investigates the enhancements to mechanical, thermal and gas barrier properties of bioplastics through addition of nanocomposites derived from clay minerals (nano clay). The resulting product was examined under Scanning Electron Microscope (SEM). This paper summarizes the clay concentrations and mixing temperature conditions that are required for the enhancement of bioplastics.